Muscle fat quantification using magnetic resonance imaging: case–control study of Charcot–Marie–Tooth disease patients and volunteers. Issue 3 (15th March 2019) - Kim, Hyun Su; Yoon, Young Cheol; Choi, Byung‐Ok; Jin, Wook; Cha, Jang Gyu
Abstract: Background: This study aimed to evaluate the potential value of 3D multiple gradient echo Dixon‐based magnetic resonance imaging (MRI) sequence as a tool for thigh intramuscular fat quantification in Charcot–Marie–Tooth disease (CMT) patients. Methods: A prospective comparison study comprising 18 CMT patients and 18 age/sex‐matched volunteers was performed. MRI including 3D multiple gradient echo Dixon‐based imaging was performed for each subject. Region of interest analyses were performed at the upper and lower third of both thighs. The two‐sample t ‐test or Wilcoxon rank sum test was used for intergroup comparison of the mean muscle fat fraction. Intraclass correlation coefficients were used to evaluate the interobserver agreement and test–retest reproducibility. Semiquantitive analysis using the Goutallier classification (Grades 0–4) was performed on T1‐weighted images in upper thigh muscles. For Goutallier Grade 0 muscles, comparison of the mean intramuscular fat fraction between volunteers and CMT patients was performed. Results: The interobserver agreements were excellent for all measurements (intraclass correlation coefficients > 0.8). Mean muscle fat fractions were significantly higher in all the measured muscles of CMT patients ( P < 0.05) except in the adductor magnus in the upper thigh ( P = 0.109). Goutallier Grade 0 muscles of the CMT patients showed a significantly higher mean fat fraction compared with that of the volunteers ( P < 0.05). Conclusions: 3D multiple gradient echo Dixon‐based MRI is a reproducible and sensitive technique which can reveal a significant difference in the fat fraction of thigh muscle, including comparison between Goutallier Grade 0 muscles, between CMT patients and volunteers.